Ответ:
(-2;8) (8;-2)
Объяснение:
Система:
Х+у=6
Х^2×у+ху^2= - 96
Х=6-у
(6-у)^2×у+(6-у)у^2= - 96
(36-12у+у^2)у+6у^2-у^3= - 96
36у-12у^2+у^3+6у^2-у^3= - 96
-6у^2+36у+96=0
D=36^2-4×(-6)×96=1296+2304=3600
У1= - 36+60 /(-12)= - 2
У2= - 36-60 /(-12)=8
Х1=6-(-2)=8
Х2=6-8= - 2
(8;-2) (-2;8)
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
(-2;8) (8;-2)
Объяснение:
Объяснение:
Система:
Х+у=6
Х^2×у+ху^2= - 96
Х=6-у
(6-у)^2×у+(6-у)у^2= - 96
(36-12у+у^2)у+6у^2-у^3= - 96
36у-12у^2+у^3+6у^2-у^3= - 96
-6у^2+36у+96=0
D=36^2-4×(-6)×96=1296+2304=3600
У1= - 36+60 /(-12)= - 2
У2= - 36-60 /(-12)=8
Х1=6-(-2)=8
Х2=6-8= - 2
(8;-2) (-2;8)